Caminho da fé: reflexões sobre lazer e ambiência - Moreira, Jaqueline Costa Castilho [UNESP]; Schwartz, Gisele Maria [UNESP] (Universidade Estadual Paulista, 2010)
This study, of qualitative nature, it aimed to investigate attitudes capable to foment pro-environmental behaviour, during one walked. The Caminho da Fé was chosen, with 425 km-itinerary trail between Tambaú and Aparecida/SP, which attracts tourists, physical activities performers and religious persons. After a literature review on the thematic one, was made an exploratory research, with a random sample, of seven adults, of both sexes, using a mixed questionnaire and Thompson e Barton's Scale of Ecocentrism and Anthropocentrism, applied in the stop places, or three times: at the beginning, in the middle of the way and at the end of the itinerary. The qualitative analysis was made by the use of Thematic Content Analysis, with results also presented in a percentile way, to illustrate. As conclusion, it is inferred that, even the stimulation has ceased with the ending of the hike, the intensity, amount and quality of the experience had stimulated reflection processes, associated to variations on physical and social environmental conditions, the predispose to the dialogue and the symbolic identification, at which, had collaborated so that the participants had been able to perceive possibilities of conduction and transitions of values and new senses for their lives.

Este estudo, de natureza qualitativa, objetivou investigar atitudes capazes de fomentar comportamentos pró-ambientais, durante uma caminhada. Escolheu-se o Caminho da Fé, com 425 km entre Tambaú e Aparecida/SP, o qual atrai turistas, esportistas e fiéis. Após revisão bibliográfica sobre a temática, foi feita uma pesquisa exploratória, com uma amostra aleatória, de sete adultos, de ambos os sexos, utilizando um questionário misto e a Escala de Thompson e Barton de ecocentrismo e antropocentrismo, aplicado nos locais de parada, por três vezes: no início, no meio e ao final do trajeto. A análise qualitativa foi feita por meio da técnica de Análise de Conteúdo Temático, com os dados apresentados percentualmente, para ilustrar. Concluiu-se que, embora os estímulos tenham cessado; sua intensidade, quantidade e qualidade desencadearam processos de reflexão, que associados às variações ambientais, físicas e sociais; a pré-disposição ao diálogo e a identificação simbólica, colaboraram para que os participantes percebessem transições de valores e novas possibilidades de condução e sentidos para suas vidas.
Caminho da fé: reflections on leisure and environment
Keywords: Leisure; Hike; Behavior; Environment; Lazer; Caminhada; Comportamento; Ambiente